The differential effects of eicosapentaenoic acid and docosahexaenoic acid on cardiovascular risk factors: an updated systematic review of randomized controlled trials - Choi, Gyu Yeong; Calder, Philip C. (Frontiers in Nutrition, 2024)
Cardiovascular disease remains a major global health concern. The combination of the omega-3 fatty acids eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) has been shown to beneficially modify a range of cardiovascular risk factors. However, whether EPA and DHA have differential effects or potencies is currently unclear. A systematic review of randomised controlled trials (RCTs) that compared > 2 g/day of near pure EPA and DHA was conducted. A total of 24 publications from 9 unique RCTs were included. EPA and DHA both lower triglyceride levels, with DHA most likely having a slightly greater effect. Furthermore, both EPA and DHA increase high density lipoprotein (HDL) 2 cholesterol, which is cardioprotective, with the increase being greater with DHA. DHA appears to increase low density lipoprotein (LDL) cholesterol; however, DHA also increases LDL particle size, which would render LDL less atherogenic. DHA seems more effective than EPA in decreasing heart rate and blood pressure. Both EPA and DHA alter platelet function decreasing thrombogenicity, although they may have different actions on platelets. Both EPA and DHA decrease F2-isoprostanes, interpreted as a reduction in oxidative stress. They both decrease inflammatory gene expression and promote an anti-inflammatory oxylipin profile. These are all favourable effects with regard to cardiovascular disease risk. Effects of EPA and DHA on blood glucose are inconsistent. This review is constrained by the small number of high quality RCTs that directly compare EPA to DHA and report on outcomes other than blood lipids. There is a need for additional high-quality research to assess the independent effects of EPA and DHA on cardiovascular risk factors (e.g. inflammation, blood pressure, vascular function, platelet function) in larger and more diverse study populations.